Between reason and history : Habermas and the idea of progress - Owen, David S. (Albany : State University of New York Press, 2002)
Annotation Jurgen Habermas's The Theory of Communicative Action attempts to clarify a normative foundation of a critical theory and is widely recognized as such, but according to Owen (philosophy, Hamline U.) not enough attention is paid to the theory of social evolution it contains. He summarizes and explains the theory, situating in the context of Habermas's wider theory and within the wider field of critical theory itself. The theory insists that there is a universal of societal development that must be distinguished from the contingencies of the historical process. This societal development is understood to occur when societies evolve to higher levels through a process in which learning occurs with respect to the society's normative structures and it occurs according to a certain pattern that can be reconstructed in terms of a developmental logic. Annotation copyrighted by Book News, Inc., Portland, OR
Further Questions -- 5. Progress and Social Evolution -- Habermas' s Conception of Progress -- The Dialectic of Progress -- A Differentiated Conception of Progress -- Summary and Conclusions -- Notes -- Notes to Introduction -- Notes to Chapter 1 -- Notes to Chapter 2 -- Notes to Chapter 3 -- Notes to Chapter 4 -- Notes to Chapter 5 -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Z.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Habermas, Jürgen.; Habermas, Jürgen.; Habermas, Jürgen; Progress -- Philosophy; Progrès -- Philosophie; SOCIAL SCIENCE -- General; Progress -- Philosophy